Pelatihan Peningkatan Keselamatan Kerja dan Penataan Laboratorium Bagi Guru Dan Peserta Didik - Amsad, Lusia Narsia; Jukwati; Wambrau, Mince Regina; Putri, Nadila Kirey (Universitas Cenderawasih, 2024)
Chemistry laboratory in Senior High School (SMA) is one of the facilities used to support chemistry learning. With the presence of a chemistry laboratory in school, students will better understand the material by doing practical activities. For that, it is also necessary to pay attention to work safety in the laboratory related to the arrangement and maintenance of the laboratory. For that, community service activities in the form of training on laboratory arrangement related to the materials and equipment in the laboratory have been carried out at SMA Pembangunan Yapis 6 Keerom. The implementation activities have gone well and have a positive impact on learning activities in the chemistry laboratory at the school.